ABCD: Update of the 2009 guidelines on prevention and management of feline infectious diseases. Issue 7 (July 2013) - Horzinek, Marian C; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hartmann, Katrin; Hosie, Margaret J; Lloret, Albert; Lutz, Hans; Marsilio, Fulvio; et al.
Overview: In this article, the ABCD guidelines published in the JFMS Special Issue of July 2009 (Volume 11, Issue 7, pages 527–620) are updated by including previously unavailable and novel information. For a better picture, the reader is advised to consult that issue before focusing on the novel features.